2020
DOI: 10.1182/blood-2020-139192
|View full text |Cite
|
Sign up to set email alerts
|

REGN5458, a BCMA x CD3 Bispecific Monoclonal Antibody, Induces Deep and Durable Responses in Patients with Relapsed/Refractory Multiple Myeloma (RRMM)

Abstract: Background Multiple myeloma (MM) is characterized by expression of the cell surface protein B-cell maturation antigen (BCMA), a validated target for therapeutic intervention. REGN5458 is a BCMA x CD3 bispecific antibody (Ab) that binds to both BCMA and CD3, thereby targeting MM cells with T-cell effector function via BCMA. Previously, we presented data showing REGN5458 has an acceptable safety profile with evidence of clinical efficacy in heavily pre-treated patients with RRMM. Here we describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 0 publications
0
47
0
Order By: Relevance
“…BiTEs and bispecific antibodies bring T-cells and targeted tumor cells in close vicinity of each other in cytolytic synapses, which leads to tumor-specific cytolytic T-cell activation and MM cell lysis [ 30 , 54 , 55 , 56 , 57 , 58 ]. BiTEs targeting the MM-associated B-cell maturation antigen (BCMA) have been associated with very promising, albeit short-lived, efficacy signals raising hopes that they may provide the foundation for effective strategies against the immune-suppressive TME in MM [ 30 , 54 , 55 , 56 , 57 , 58 ] ( Figure 2 ). Bispecific BCMAxCD3 antibodies such as Regeneron’s REGN5458 also showed clinical potential with promising data from recent clinical trials in R/R MM patients [ 54 ] ( Figure 2 ).…”
Section: Clinical Impact Potential Of Bispecific T-cell Engagers and mentioning
confidence: 99%
“…BiTEs and bispecific antibodies bring T-cells and targeted tumor cells in close vicinity of each other in cytolytic synapses, which leads to tumor-specific cytolytic T-cell activation and MM cell lysis [ 30 , 54 , 55 , 56 , 57 , 58 ]. BiTEs targeting the MM-associated B-cell maturation antigen (BCMA) have been associated with very promising, albeit short-lived, efficacy signals raising hopes that they may provide the foundation for effective strategies against the immune-suppressive TME in MM [ 30 , 54 , 55 , 56 , 57 , 58 ] ( Figure 2 ). Bispecific BCMAxCD3 antibodies such as Regeneron’s REGN5458 also showed clinical potential with promising data from recent clinical trials in R/R MM patients [ 54 ] ( Figure 2 ).…”
Section: Clinical Impact Potential Of Bispecific T-cell Engagers and mentioning
confidence: 99%
“…In addition, the second-generation HLE-BiTE AMG 701 has achieved an 83% ORR in patients with R/R MM, the majority of responders experienced triple therapy failure [59]. Teclistamab [60], REGN5458 [61], CC-93269 [62] PF-06863135 [63], and TNB-383B [64] are other investigational T-cell engaging bsAbs designed to bind to BCMA with structural differences, all of them have entered the early clinical stage for treating patients with R/R MM with promising efficacy. The clinical advances of these newly developed BiTE antibodies and other T-cell engaging bsAbs are summarized in Table 3.…”
Section: Clinical Advances Of Bite In Hematological Malignanciesmentioning
confidence: 99%
“…Updated safety and response durability in a Phase 1 trial of REGN5458 monotherapy in patients with RRMM were recently reported at the 2020 ASH meeting. (NCT03761108) [ 65 ]. Enrolled patients must have progressive MM after ≥3 prior lines of systemic therapy, including a PIs, IMIDs, and an anti-CD38 Ab.…”
Section: Bispecific Monoclonal Antibodies: Design and Mechanism Ofmentioning
confidence: 99%